Sharḥ-i Naẓm al-durr : Sharḥ-i qaṣīda-yi tāʾiyya-yi kubrā-yi Ibn-i Fāriḍ - Iṣfahānī, Ibn Turka, (Miras Maktoob, ISBN: 9789004365452., 2019)
Ibn al-Fāriḍ (d. 632/1235) is arguably the greatest mystical poet in the history of Arabic literature. Born in Cairo and a student of Shāfiʿī law and ḥadīth in his younger years, he turned to mysticism, living a solitary existence on Cairo's Muqaṭṭam hills, in the desert, and in the Hijaz. After his return to Cairo, people worshipped him as a saint, and even today admirers still visit his tomb. Ibn Turka Iṣfahānī (d. 835/1432) stemmed from a well-educated family in Isfahan. A survivor of Tīmūr Lang's (d. 807/1405) massacre of the population of Isfahan in 789/1387, he first studied the Islamic sciences with his elder brother in Samarqand, after which he went on a study tour which took him to such great scholars as Shams al-Dīn Fanārī (d. 834/1451) and Sirāj al-Dīn al-Bulqīnī (d. 805/1403). A specialist of mysticism in its relation to philosophy and Islam, this is his commentary on Ibn al-Fāriḍ's al-Tāʾiyya al-kubrā.